2010
DOI: 10.1124/mol.109.062174
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Neurotoxic Pesticide Increases Histone Acetylation to Promote Apoptosis in Dopaminergic Neuronal Cells: Relevance to Epigenetic Mechanisms of Neurodegeneration

Abstract: Pesticide exposure has been implicated in the etiopathogenesis of Parkinson's disease (PD); in particular, the organochlorine insecticide dieldrin is believed to be associated with PD. Emerging evidence indicates that histone modifications play a critical role in cell death. In this study, we examined the effects of dieldrin treatment on histone acetylation and its role in dieldrin-induced apoptotic cell death in dopaminergic neuronal cells. In mesencephalic dopaminergic neuronal cells, dieldrin induced a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
126
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(136 citation statements)
references
References 47 publications
6
126
1
Order By: Relevance
“…The exposure to Dieldrin, a neurotoxic pesticide associated with PD etiopathogenesis, was shown to induce histone H3 and H4 hyperacetylation via the timedependent CBP accumulation in dopaminergic neurons [111]. Alternatively, wild-type α-synuclein reduces p300 expression level and HAT activity.…”
Section: Pdmentioning
confidence: 99%
“…The exposure to Dieldrin, a neurotoxic pesticide associated with PD etiopathogenesis, was shown to induce histone H3 and H4 hyperacetylation via the timedependent CBP accumulation in dopaminergic neurons [111]. Alternatively, wild-type α-synuclein reduces p300 expression level and HAT activity.…”
Section: Pdmentioning
confidence: 99%
“…An optimal balance between HAT and HDAC activity is required for cell survival, and disruption of this balance has been implicated in neurodegenerative diseases (40). We previously reported that neurotoxic pesticide exposure induced hyperacetylation of histones H3 and H4, which contributed to cell death in cell culture models of PD (41)(42)(43). Similarly, overexpression of a HAT, Tip60, was found to induce neuronal apoptosis in Drosophila (44).…”
mentioning
confidence: 99%
“…Histone acetylation may represent a key epigenetic modification in dopaminergic neuronal cells due to neurotoxic insults. The exposure of paraquat to N27 dopaminergic cells induced histone H3 acetylation and decreased the total HDAC activity [63,64]. Similarly, dieldrin induced a time-dependent increase in the acetylation of core histones H3 and H4 [63].…”
Section: Epigenetic Modifications In Idiopathic Pd and Due To Environmentioning
confidence: 91%
“…In mouse models, exposure to dieldrin induced histone acetylation in the nigrostriatal system. Anacardic acid, a HAT inhibitor, significantly attenuated dieldrin-induced histone acetylation and dieldrin-associated apoptosis, which was independent of its antioxidant effect [63]. In addition, administration of MPTP in murine and non-human primate models has been associated with decreased striatal presence of H3 histone K4 trimethylation, and chronic administration of the DA precursor L-DOPA has been demonstrated to reverse these changes [65].…”
Section: Epigenetic Modifications In Idiopathic Pd and Due To Environmentioning
confidence: 95%
See 1 more Smart Citation